2006
DOI: 10.1534/genetics.105.051912
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Trait Locus Analysis of Atherosclerosis in an Intercross Between C57BL/6 and C3H Mice Carrying the Mutant Apolipoprotein E Gene

Abstract: Inbred mouse strains C57BL/6J (B6) and C3H/HeJ (C3H) differ significantly in atherosclerosis susceptibility and plasma lipid levels on the apolipoprotein E-deficient (apoE ÿ/ÿ ) background when fed a Western diet. To determine genetic factors contributing to the variations in these phenotypes, we performed quantitative trait locus (QTL) analysis using an intercross between the two strains carrying the apoE ÿ/ÿ gene. Atherosclerotic lesions at the aortic root and plasma lipid levels of 234 female F 2 mice were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
64
4

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 45 publications
(73 citation statements)
references
References 43 publications
5
64
4
Order By: Relevance
“…ApoE knock-out (ko) mice were purchased from Jackson laboratories after being generated from B6.apoE −/− at the N10 backcross and constructed from B6.129 apoE −/− mice [20]. C57BL/6J wild types were purchased from Charles River Laboratories (Wilmington, MA).…”
Section: Undernutrition Modelmentioning
confidence: 99%
“…ApoE knock-out (ko) mice were purchased from Jackson laboratories after being generated from B6.apoE −/− at the N10 backcross and constructed from B6.129 apoE −/− mice [20]. C57BL/6J wild types were purchased from Charles River Laboratories (Wilmington, MA).…”
Section: Undernutrition Modelmentioning
confidence: 99%
“…Mice were fed a Western diet containing 42% fat, 0.15% cholesterol and 19.5% casein for 12 weeks. The phenotypic measurements, including atherosclerotic lesion size, of F2 mice were previously reported [13]. Vcam1 genotypes of F2 mice were determined by the PCR-RFLP method.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, in the F2 population derived from B6.apoE −/− and C3H.apoE −/− mice, the association between Vcam1 genotypes and atherosclerotic lesion size was not detected. The confounding influence of atherosclerosis susceptibility loci on chromosomes 9 and 11 [13] may have diminished the power to detect associations between Vcam1 and atherosclerotic lesions using the cross. Another explanation is that VCAM-1 contributed less significantly to the development of atherosclerosis in the apoE −/− model than in the diet-induced model.…”
Section: Discussionmentioning
confidence: 99%
“…FFA concentrations were affected by a significant locus on Chr 4, a suggestive locus on Chr 16, and two interacting loci on Chr 2 and 15. Plasma glucose concentrations were affected by QTL on Chr 2,4,7,8,10,15,17,and 18. Comparative genomics narrowed the QTL by 31% to 86%; haplotype analysis was usually able to further narrow it by 80%.…”
mentioning
confidence: 99%
“…Because of inherent difficulties in carrying out linkage analyses for complex traits in humans, inbred strains of mice have been used as a powerful tool for identifying quantitative trait loci (QTL) that contribute to variations in circulating levels of lipids and glucose (7)(8)(9). Studies in mice not only have revealed a large number of QTL that regulate lipid levels but also have shown that there is a high degree of concordance with human QTL that regulate the same traits (7).…”
mentioning
confidence: 99%